2008
DOI: 10.1016/j.ydbio.2007.10.013
|View full text |Cite
|
Sign up to set email alerts
|

JAM-A is present in mammalian spermatozoa where it is essential for normal motility

Abstract: Junctional adhesion molecules (JAMs) that are expressed in endothelial and epithelial cells and function in tight junction assembly, also perform important roles in testis where the closely-related JAM-A, JAM-B, and JAM-C are found. Disruption of murine Jam-B and Jam-C has varying effects on sperm development and function; however, deletion of Jam-A has not yet been studied. Here we show for the first time that in addition to expression in the Sertoli-Sertoli tight junctions in the seminiferous tubules, the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 31 publications
(47 reference statements)
5
50
0
Order By: Relevance
“…indicates that JAM-A is found on both Sertoli and a subset of basal GCs in the testis, a finding that is supported by microarray data from Sertoli and GC isolates (Chalmel et al 2007), as well as the identification of JAM-A protein in spermatozoa from the caudal epididymis (Shao et al 2008). Together, these data suggest a novel role for JAM-A in spermatogenesis.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…indicates that JAM-A is found on both Sertoli and a subset of basal GCs in the testis, a finding that is supported by microarray data from Sertoli and GC isolates (Chalmel et al 2007), as well as the identification of JAM-A protein in spermatozoa from the caudal epididymis (Shao et al 2008). Together, these data suggest a novel role for JAM-A in spermatogenesis.…”
Section: Discussionmentioning
confidence: 52%
“…JAM family members (JAM-B and JAM-C) have been identified on both Sertoli and GCs in rodents, while claudins and occludin have been localised exclusively to inter-Sertoli cell TJs in this species . To date, JAM-A has been identified at inter-Sertoli cell junctions and the tails of elongated spermatids within the epididymis of rodents (Shao et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This difference could be related to the mode of fertilization, in vivo or in vitro. JAM-A is present in elongated spermatids and in the plasma membrane of the head and flagellum of sperm [20], and plays an important role in cell adhesion [21]. Since in vitro fertilization occurs in fish, the high expression of JAM-A in fish eggs may be more conducive to egg and sperm cell adhesion and subsequent sperm penetration into the egg membrane.…”
Section: Discussionmentioning
confidence: 99%
“…lacking Jam-A (Shao, Ghosh, Cooke, Naik, & Martin-DeLeon, 2008) and have shown that it is associated with decreased activity of PMCA4 (Aravindan et al, 2012).…”
mentioning
confidence: 99%
“…Breeding and genotyping of these mice were described previously (Okunade et al, 2004). Jam-A null sperm were generated and genotyped as described (Shao et al, 2008). …”
mentioning
confidence: 99%